THE INFLUENCE OF CREDIT RISK AND LIQUIDITY RISK ON THE PERFORMANCE OF BANKS LISTED ON THE INDONESIAN STOCK EXCHANGE - Zalfa Zafira Priana; Siti Laksmi Maharani; Farah Margaretha Leon (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
In recent years, the banking sector in Indonesia has attracted significant attention due to its role in the country's economic development. As a vital component of the financial system, banks play a crucial role in allocating funds, supporting economic activities, and ensuring financial stability. Amidst the evolving landscape of financial markets and regulatory changes, understanding the factors that influence the performance of conventional banks has become a pertinent area of research. This study aims to test and analyze the effect of credit risk, measured by non-performing loans, and liquidity risk, measured by liquid assets to total assets, as well as control variables such as bank size, gross domestic product, and inflation on bank performance, measured by return on assets in 39 conventional banks listed on the Indonesia Stock Exchange for 5 years (2016 - 2020). This study employs a quantitative approach, utilizing panel data analysis – a blend of time series and cross-sectional data. The results of the analysis show that non-performing loans have a negative and significant effect on return on assets. Liquid assets to total assets also have a negative and significant effect on return on assets. The control variable of bank size has a positive and significant effect on return on assets. Similarly, the control variable of gross domestic product has a positive and significant effect on return on assets. Additionally, the inflation control variable has a positive and significant effect on return on assets.